How to FInance Colleges - Tatyana Klyachko (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
The purpose of this article is to construct and analyze the ways to standardize per capita financing of colleges. The article considers the main problems encountered by colleges and government bodies in implementing the «money follows the student» principle. The author discusses how these methods should be adapted if some of the students pay for tuition, while the rest do not. Significant attention is paid to the differentiation of per capita funding depending on the real costs of different educational programs. The author also attempts to provide for a new organizational and legal status for colleges that is becoming available, namely that of an autonomous institution.